A repairable anhydride-epoxy system with high mechanical properties inspired by vitrimers. (20th December 2018) - Yang, Yang; Peng, Guirong; Wu, Shu; Hao, Wenguang
Abstract: In this paper, a hard epoxy material based on a mature curing system was prepared. The addition of 2 mol% transesterification catalyst showed the best strengthening effect, as well as satisfactory thermal welding and repairing property. With rheological experiment, a double stress relaxation theory was proposed and a multi-element model was established. Among the two relaxation processes, one was caused by small units in response to external force, the other was caused by chain segments sped up by the transesterification, and the whole relaxation was the superposition of these two parts. A further post-curing process caused by catalyst was found by the DSC analysis. It was the further post-curing process that resulted in the formation of inactive crosslinks without relaxation ability. Therefore, this repairable hard epoxy material still had a service life and couldn't be repaired infinitely. However, it provides a new way to prepare repairable hard materials. Graphical abstract: Highlights: The system is a hard material unlike normal vitrimer. An interesting further post curing effect caused by catalyst is found and explained. A double relaxation theory is proposed and the corresponding model is also establish.